1998
DOI: 10.1097/00006254-199809000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Cholecystectomy During Pregnancy

Abstract: This study was conducted to evaluate the role of antepartum laparoscopic cholecystectomy (LC). Patients who underwent LC were identified from a hospital database with the use of CPT/ICD codes. Of 2093 cases performed at a major center (October 1991 to November 1997), only six were performed during pregnancy. On reviewing the English literature, gestational age at surgery and delivery and outcome of delivery were provided in only 69 of 105 patients (33 papers with 1-10 cases) and we tabulated different variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…The management of symptomatic biliary disease during pregnancy has often been nonsurgical to avoid fetal and maternal harm ( 10 ) , but ironically, this results in a high rate of antepartum symptom recurrence ( 2 , 8 , 9 ) . Although laparoscopy is known to be safe in the second trimester, studies have reported the risk of preterm labor or spontaneous abortion with LC ( 12 , 13 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The management of symptomatic biliary disease during pregnancy has often been nonsurgical to avoid fetal and maternal harm ( 10 ) , but ironically, this results in a high rate of antepartum symptom recurrence ( 2 , 8 , 9 ) . Although laparoscopy is known to be safe in the second trimester, studies have reported the risk of preterm labor or spontaneous abortion with LC ( 12 , 13 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Recent guidelines recommended LC during pregnancy for all symptomatic gallstone disease ( 8 , 9 ) and laparoscopic treatment of acute abdominal disease has the same indications in pregnant and non-pregnant patients ( 18 ) . Studies reporting uterine injury during trocar placement, increased risk of preterm labor and spontaneous abortion with LC exist, even though they were performed in the second trimester ( 12 , 13 ) . The rate of preterm labor is 0-20% for LC ( 19 , 20 , 21 , 22 , 23 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Generally, open cannulation laparoscopy or Palmer's point entry is recommended for laparoscopy during pregnancy. This avoids the risk of penetrating injury to the pregnant uterus by either the Verres needle or the trocar cannula [13]. …”
Section: Discussionmentioning
confidence: 99%
“…Conversion rates are from 1.8 to 7.8%. [28] Specific complications include hemorrhage, bile leaks, retained stones, wound infections and incisional hernias. [92829]…”
Section: Discussionmentioning
confidence: 99%
“…The key points associated with higher success rate in laparoscopic cholecystectomy during pregnancy: Experienced surgeon[28]Trendelberg and left tilted position[20–22]Insertion of the first trocar with great precussion especially in late pregnancy to avoid injury of gravid uterus[18]Pneumoperitoneum created with an average intraabdominal pressure of 10–12 mmHg[23]Adequate Mother monitoring (adequate management of anesthetic, adequate hydration of mother to reduce the likelihood of premature labor) and treating the contractions with tocolytics. [4]…”
Section: Discussionmentioning
confidence: 99%